Association between the environmental quality index and textbook outcomes among Medicare beneficiaries undergoing surgery for colorectal cancer (CRC). Issue 7 (11th March 2023) - Shaikh, Chanza F.; Woldesenbet, Selamawit; Munir, Muhammad Musaab; Moazzam, Zorays; Endo, Yutaka; Alaimo, Laura; Azap, Lovette; Yang, Jason; Katayama, Erryk; Lima, Henrique A.; Dawood, Zaiba; Pawlik, Timothy M.
Abstract: Background: Quality of cancer care received by individuals may be influenced by environmental factors resulting in inequalities within the healthcare system. We sought to investigate the association between the Environmental Quality Index (EQI) and achievement of textbook outcomes (TOs) among Medicare beneficiaries who underwent surgical resection for colorectal cancer (CRC). Methods: Patients diagnosed with CRC from 2004 to 2015 were identified using the Surveillance, Epidemiology, and End Results‐Medicare database and merged with the US Environmental Protection Agency's EQI data. A high EQI category indicated poor environmental quality, whereas a low EQI indicated better environmental conditions. Results: Among 40 939 patients, 33 699 (82.3%) were diagnosed with colon cancer, 7240 (17.7%) were diagnosed with rectal cancer, and 652 (1.6%) were diagnosed with both cancers. Median age was 76 years old (interquartile range: 70–82 years) with roughly half of patients being female ( n  = 22 033, 53.8%). Most patients self‐reported as White ( n  = 32 404, 79.2%) and resided in the West region of the United States ( n  = 20 308, 49.6%). On multivariable analysis, patients residing in high EQI areas were less likely to achieve TO (referent: low EQI; odds ratio [OR]: 0.94, 95% confidence interval [95% CI]: 0.89–0.99; p  = 0.02). Of note, Black patients living in moderate‐to‐high EQI counties had a 31% decreased likelihood of reaching a TO compared with White patients in low EQI counties (OR: 0.69, 95% CI: 0.55–0.87). Conclusion: Patients residing in high EQI counties and Black race were associated with a lower likelihood of TO following resection of CRC among Medicare patients. Environmental factors may be important contributors to health care disparities and affect postoperative outcomes following CRC resection.